Negative pressure wound therapy: A systematic review of randomized controlled trials from 2000 to 2017. Issue 2 (20th November 2018) - Peinemann, Frank; Labeit, Alexander
Abstract: Background: Negative pressure wound therapy (NPWT) proposes to provide better wound healing than standard wound management. Evidence quality of randomized controlled trials (RCTs) varies. Methods: We included participants with any kind of wounds and commercial as well as the homemade NPWT system. Comparators were any other wound dressing including variant NPWTs. We included RCTs randomizing patients or wounds in parallel or crossover designs. We searched PubMed and Cochrane Library on January 03, 2018. We assessed the risk of bias according to Cochrane and appropriateness of clinical endpoints according to the Food and Drug Administration (FDA). Results: We included 93 RCTs originating in 30 countries, 70 studies on open wounds and 23 studies on closed wounds. With respect to random sequence generation, we judged an unclear or high risk of bias in 50% (47 of 93) studies. With respect to allocation concealment, we judged an unclear or high risk of bias in 90% (84 of 93). We identified 41% (38 of 93) studies that based their conclusion on not appropriate endpoints. Conclusions: High risk of bias concerning random sequence generation and allocation concealment limited the credibility of the majority of 93 included RCTs on NPWT. A low risk of bias can and should be achieved with both items, and we recommend to align future RCTs to Cochrane. Many primary clinical endpoints were deemed not valid for making inferences on the efficacy of NPWT. We recommend using patient‐centered endpoints as requested by the FDA and suggested in the present systematic review.